Existence Of Copyration Laws Related To The Principle Of Openness Which Are Not Completed In The Process Of Its Establishment - Monica Virga Darmawan; Rachel Anne Patricia; Calvita Calvita; Ayesha Tasya Izulkha (LEGAL BRIEF, 2022)
Good governance can be realized with the implementation of the formation of laws and regulations in accordance with the principles, especially the principle of openness. The importance of implementing the principle of openness is to make it easier for the public to provide input orally and/or in writing. Each Draft Legislation must be easily accessible to the public, with the aim that the government works fairly and transparently, and the public can also better understand how the government works, both in preparation, implementation and maximum results achieved. This study uses qualitative data with a normative juridical method or approach. The conclusion of this study is that there must be participation from the public starting from the stage of drafting the Law to the end, during the discussion stage in the DPR it must be carried out in a transparent, careful and unhurried manner. Also, the substance must be ensured that it meets the material and formal requirements in the formation of statutory regulations as stipulated in Law Number 12 of 2011 concerning the formation of statutory regulations.